THE EFFECTIVENESS OF SIMULATION EDUCATION FOR UNDERGRADUATE STUDENTS IN SOFTWARE ENGINEERING AREA - Ahmad, S.; Muda, N. A.; Muda, A. K.; A. Jalil, I.E. (2011)
Simulation in education is a replacement model for real world experience. This approach is seen effective to give undergraduate students the opportunity to apply their theoretical knowledge and practice their skills learnt in laboratory. Simulation education is designed to emphasize outcome based education or known as OBE to bridge the gap between theory and practice. Implementing simulation model to represent real world practice in industry, undergraduate students are trained to deal with real problems in the right atmosphere. The effort eventually prepares the students to face a real working environment when they are graduated from the university. This paper discusses the curriculum designed for simulation education applied for undergraduate students in university, its implementation and the analysis of the outcome product. A specific case of Universiti Teknikal Malaysia Melaka is presented here.